Direct Synthesis of Methanol by Partial Oxidation of Methane with Oxygen over Cobalt Modified Mesoporous H-ZSM-5 Catalyst - Yuni Krisyuningsih Krisnandi; Bayu Adi Samodro; Riwandi Sihombing; Russell Francis Howe (Universitas Gadjah Mada, 2015)
Partial oxidation of methane over mesoporous catalyst cobalt modified H-ZSM-5 has been carried out. Mesoporous Na-ZSM-5 (Si/Al = 35.4) was successfully synthesized using double template method which has high surface area (450 m2/g) and average pore diameter distribution of 1.9 nm. The as-synthesized Na-ZSM-5 was converted to H-ZSM-5 through multi-exchange treatment with ammonium ion solution, causing decreased crystallinity and surface area, but increased porous diameter, due to dealumination during treatment process. Moreover, H-ZSM-5 was loaded with cobalt (Co = 2.5% w) by the incipient impregnation method and calcined at 550 °C. Partial oxidation of methane was performed in the batch reactor with 0.75 bar methane and 2 bar of nitrogen (with impurities of 0.5% oxygen) as the input at various reaction time (30, 60 and 120 min). The reaction results show that cobalt species in catalyst has an important role, because H-ZSM-5 cannot produce methanol in partial oxidation of methane. The presence of molecular oxygen increased the percentage of methanol yield. The reaction is time-dependent with the highest methanol yield (79%) was acquired using Co/H-ZSM-5 catalyst for 60 min.